The Existence Of Jemblung Islamic Art : at the Jemblung Sanggar Proff Jim Kediri City - Ken Nirmalasari (Solah, 2025)
Islamic Jemblung art in Kediri City, East Java, Indonesia, is a form of oral performance art that has developed within the community. The Jemblung Studio, led by Proff. Jim, serves as a custodian of this art form, even as fewer people become familiar with it. This research aims to reintroduce this art through field studies conducted on Jl. Raung, Lirboyo, Mojoroto District, Kediri City. A qualitative research method is employed, utilizing techniques such as interviews, documentation, and observation of the studio and its owner. Grounded in the theory of existence, this study discusses preservation strategies, comparisons with other art forms, and modern challenges. The findings indicate that Jemblung art has a rich history deeply rooted in local culture, which has transformed with the introduction of Islamic values. The Jemblung Studio, led by Proff. Jim, plays a crucial role in cultural preservation by engaging the younger generation through training programs and regular performances. Furthermore, comparing Jemblung art with other Islamic arts, such as Qasidah and Hadrah, reveals both uniqueness and similarities in conveying religious messages. Despite facing challenges such as decreasing government support and waning interest from the younger generation, the studio capitalizes on opportunities through innovation and creativity, including the use of social media for promotion. Keywords: Jemblung Art, Cultural Existence, Kediri City